(untitled) (Eurasian Journal of Philology Science and Education, 2019)
The article is devoted to the features of the translation of linguistic means of expressing a threat, namely, menacing speech acts of political discourse from English to Russian. Translation of menacing speech acts of political discourse come out as a binary communicative aesthetics and is a product of linguistic and cultural interferences. Essentially, an intertextual interpenetration of two different phenomena occurs between the original and its translation as well, which could give a different semantic and aesthetic background. And this is clearly seen in the texts of speeches in threatening speech acts of both the President of the United States of America D. Trump and the North Korean leader Kim Jongun. Menacing speech acts in political discourse are discrete, they are diverse in content and form as well. In such political texts, phraseological units, neologisms, literary tools, folk elements (proverbs and sayings, anecdotes, parables and myth, etc.) can suddenly appear. They complicate the translation process and cause linguistic and psychological interference. In this regard, the speech acts of threats to US President D. Trump are indicative, whose speech often uses metaphorical statements, which is difficult in the process of translation, but at the same time interesting for our research as well.